Удосконалення математичної моделі руху для задачі керування підйомно-транспортними машинами - Григоров, Отто Володимирович; Окунь, Антон Олександрович (Харківський національний автомобільно-дорожній університет, 2017)
Стаття присвячена удосконаленню математичної моделі руху системи «візок–вантаж» у задачі керування кабельним краном. Отримані рівняння руху можуть бути використані для побудови фазових траєкторій системи «візок–вантаж» та для знаходження керування кабельним краном.

The article deals with the study of a mathematical model that describes the cable crane «carriage-cargo» system motion, taking into account the carriage movement resistance, the wind strength and the friction forces. The obtained system equations can be used to build the controllability function for the «carriage-cargo» system and determine the cable crane control by minimizing the operation cycle time by cargo oscillation damping.
Improvement of the «carriage-cargo» system motion mathematical model for solving the problem of lifting and transport machines control
Keywords: кабельний кран; система «візок–вантаж»; демпфірування коливань; cable crane; «carriage-cargo» system; oscillation dumping